Associations of lipid profiles with the risk of ischemic and hemorrhagic stroke: A systematic review and meta-analysis of prospective cohort studies - Gong, Xiaoxian; Chen, Luowei; Song, Bo; Han, Xiang; Xu, Weihai; Wu, Bo; Sheng, Feng; Lou, Min (Frontiers in Cardiovascular Medicine, 2022)
Background and purpose The associations of lipid profiles with the risk of ischemic stroke (IS) or hemorrhagic stroke (HS) are controversial. In this study, we aimed to illustrate the optimal level for lipid levels in the risk of IS and HS. Materials and methods We searched the electronic database of PubMed, Embase, and the Cochrane library from inception until November 2020. Prospective cohort studies published in English for the associations of lipid profiles (TC, TG, LDL-C, HDL-C, and non–HDL-C) with the risk of IS and HS were eligible for this study, and the publication status was not restricted. We calculated the pooled effect estimates using the random-effects model. We tested the associations of lipid profiles with IS and HS and compared their differences. Results We retrieved 50 prospective cohort studies containing 3,301,613 individuals. An increase in total cholesterol (TC) is associated with an increased IS risk (P < 0.001) and a reduced HS risk (P < 0.001). Similarly, an increase in triglyceride links with a greater IS risk (P < 0.001) but with a lower HS risk (P = 0.014). On the opposite, high-density lipoprotein cholesterol (HDL-C) correlates with a reduced IS risk (P = 0.004) but has no significant association with the HS risk (P = 0.571). Moreover, an increase in low-density lipoprotein cholesterol (LDL-C) or non–high-density lipoprotein cholesterol has no statistically significant effect on both IS and HS. The pooled effect estimates on the risk of IS and HS revealed that TC and LDL-C levels should be controlled under 6.0 and 3.5 mmol/L, respectively, to reduce worsening effects on the IS risk while maintaining potential beneficial effects on reducing the HS risk. Conclusion We revealed comprehensive relationships between lipid profiles and the risk of stroke, suggesting controlling the TC and LDL-C levels under 6.0 and 3.5 mmol/L, respectively, to balance both the IS and HS risk.